KIR receptors and HLA-C in the maintenance of pregnancy - Flores, Ana Claudia (2007)
The present study demonstrated that patients who have recurrent spontaneous abortions (RSA) presented a decreased number of killer immunoglobulin-like inhibitory receptors (KIR), in particular KIR2DL2. The KIR AA genotype was found increased in comparison with controls. Individuals AA will also be homozygous for 2DL3, which in contrast to 2DL2, show a weaker interaction with C1 ligands and therefore a weaker inhibition. The present study might support that in RSA patients, the balance between inhibitory and activating receptors present in natural killer cells is inclined toward an activating state that may contribute to pregnancy loss.